Adolescents' Internet Use: Academic Achievement and Well-being - Eir Arnbjarnardóttir 1990- (2015)
Internet use is gradually becoming more of an important factor in modern society, of which majority of users are adolescents and young people. Internet use has been connected with impairment and change in academic performance, mood, daily routines and relations with family members, for adolescents and young people. The aim of the study was to examine students’ internet use and how it may connect to academic achievement, alcohol consumption, depression and self-esteem. The participants were 175 students from three different schools in Iceland. A t-test, ANOVA, cross-tables and correlation calculations were used to do a comparison between the students’ gender, age and school, in internet use. The results showed that male and female students are using the internet quite differently. Also, there was a negative correlation between students’ internet use and how well they did at school. Furthermore, there was a negative correlation between students’ internet use and self-esteem, but a positive correlation between internet use and depression. Keywords: internet use, adolescents, academic achievement, alcohol consumption, self-esteem, depression Internet notkun er að aukast í nútíma samfélagi og þá sérstaklega hjá unglingum og ungu fólki. Netnotkun unglinga hefur verið tengd við breytingar á velgengni í skóla, skapi, daglegum athöfnum og sambandi við fjölskyldu. Markmið rannsóknarinnar var að skoða betur netnotkun unglinga og hvernig sú notkun tengist velgengni í skóla, áfengisdrykkju, depurð og sjálfsvirðingu. Allt að 175 nemendur frá þremur mismunandi skólum tóku þátt, en skólarnir voru frá mismunandi stöðum landsins. T-próf, ANOVA, krosstöflur og fylgnipróf voru notuð til að gera samanburð á netnotkun unglinga eftir kyni þeirra, aldri og skóla. Niðurstöðurnar leiddu í ljós mismunandi netnotkun nemenda eftir kyni þeirra. Það var neikvæð fylgni á milli netnotkunar unglinga og hversu vel þeir stóðu sig í skóla. Einnig var neikvæð fylgni á milli netnotkunar unglinga og sjálfsvirðingar, en jákvæð fylgni á milli ...